Análisis de eficiencia térmica del proceso de generación de vapor en la quesera Brayan del cantón Salcedo. - Saca Plasencia, Jofre Israel (2021)
The necessity to reduce excessive fuel consumption, thermal losses and the poor technical condition of the equipment involved in the generation and distribution of steam at ‘Quesera Brayan’ in Salcedo Canton, is consistent with the performance of financial statement of the factory, such as generation, transport and amount of steam used in a production line. The theoretical requirements were sufficient to carry out a thermal analysis of the system and to be able to verify with greater precision the place where there is a higher losses percentage. Therefore, it was found that it is located in the burner with 33%, and the pipe with 21.25% of losses, as a result the improvement of the technical state of the machinery was carried out, giving a compete corrective maintenance such as, changed structural parts of the steam generator, internal piping, insulation, welding under regulations, parts in its entirety of the steam transport system, regulation of the burner between air and fuel, until reaching a reduction in losses and an increase in efficiency. The before and after technical improvement was evident, counting on a thermal efficiency of steam generation and transport of the ‘Quesera Brayan del Canton Salcedo’. Before the technical improvement of 51% an annual fuel expense of $ 5,079.60 was generated and after the improvement of the technical state of this system, a notable increase in efficiency of 68% was evidenced, and a decrease in the annual economic expenses in fuel of $ 3382.20, after the technical improvement, the increase of 17% in its total efficiency was evident, and an annual economic saving of 33.41%, that represents $ 1,697.40 less in fuel expenses.